Evaluasi Pendidikan Inklusi di Sekolah Dasar Negeri - Janawati, Ni Luh Putu Gopi; Supena, Asep; Akbar, Zarina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to evaluate the implementation of inclusion education program in Gerantung State Elementary School, Central Lombok. The approach used in the research is descriptive qualitative CIPP model (Context, Input, Process, Product). Data collection in this study using interview, observation, and documentation techniques with research subjects are principals and teachers. The results of the research, in the context evaluation showed that the school officially implemented inclusion education because it had obtained permission and guidance to implement inclusion programs from the regional education office. The results of the input evaluation showed that there are three types of children with special needs (ABK) in the school, namely slow learning, learning difficulties, and hyperactivity. ABK gets learning using a curriculum that has been modified by the general teacher because it does not have a special tutor. In addition, the results of input evaluation showed that the school already has supporting facilities and infrastructure for ABK but not used properly. The results of the evaluation process show that teachers make learning planning and mentoring to students outside of lesson hours. Product evaluation results show that the academic achievement of students with special needs is left with normal students while non-academic achievement students with special needs can compete with normal students. In conclusion, the implementation of inclusion education program at SD Negeri Gerantung has been running officially, there are already facilities and infrastructure supporting ABK although it has not been optimally utilized, teachers have made a learning plan. Keywords: Children with Special Needs, Program Evaluation, CIPP Model, Inclusion Education